Budget Literacy and Financial Performance of Saccos in Kumi District-Uganda - Lawrence Etoromat (American Scientific Research Journal for Engineering, Technology, and Sciences, 2021)
This research paper is presented on the topic, “Budget literacy and financial performance of SACCOs in Kumi district”. The overall objective of the study was to determine the effect of budget literacy on financial performance of SACCOs in Kumi district. The researcher used a case study research design because of its ability to investigate the study variable in detail and due to the fact that it provides a systematic description that is factual and accurate as possible. The population under study was 343(N) people and a sample population of 108 (n) people consisting of; District commercial officer, commercial officers, SACCO board members, SACCO management team members and SACCO members. In the determination of the sample size the researcher used both probability and non-probability sampling techniques. Under data collection, the researcher used three data collection methods; firstly the researcher used Questionnaire survey method as it allowed an in depth research and collection of firsthand information in a short period of time, secondly the researcher used interview method on seven (07) key informants i.e. commercial officers (04) and Board members (03) as this was intended to probe for more information, get clarification and capture facial expression. Lastly documentary review method was used which provided necessary background and much more needed information. Three tools in this context were used i.e. Research Questionnaire, interview guide and documentary review check list. The collected data was both quantitative and qualitative in nature. Quantitative data was analysed using Statistical Package for Social Scientists (SPSS) version 25*64 bit so as to identify the missing variables. Qualitative data was recorded in the researchers note book which was transcribed for a clear meaning. The research findings highlighted the following; Budget literacy had a strong positive relationship with financial performance of SACCOs evident with R = 0.743 with p<0.01 and R2 =0.552 or 55.2%. The researcher based on the study findings recommended that; based on the overall objective; there must be creation of awareness and corporative member education, preparation of a well comprehensive budget and development of a suitable criterion for measuring the performance of management.